PERSEPSI MAHASISWA TERHADAP BAHAYA NARKOTIKA: STUDI KASUS PADA MAHASISWA POLITEKNIK - Respati Prajna Vashti; Mirza Mahbub Wijaya; Maharani; Amirah Rahma Barlinda , (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
This study will complement previous research that has not comprehensively investigated student perceptions of the dangers of drug abuse at the Jakarta State Polytechnic, by considering contemporary factors such as the influence of social media and modern lifestyles, which are strongly suspected of influencing student perceptions. Student perceptions of the dangers of drug abuse include knowledge, side effects, and legal understanding. In the context of higher education, students are at an age that is vulnerable to environmental influences and promiscuity, so how important this study is to assess student understanding of drug issues. This research method is descriptive quantitative, located at the Jakarta State Polytechnic with a sample of active students in the 2nd and 4th semesters divided into 6 study programs. The survey results found that the majority of students have a good level of knowledge about narcotics, with 59.7% stating that they are very aware and aware of the dangers of narcotics. Furthermore, 90.4% of students understand the negative impacts of drug abuse, indicating a high awareness of the physical, psychological, and social risks of these substances. On the other hand, 93.3% of students agree or somewhat agree that drug abuse is a violation of the law, reflecting good legal awareness. However, a small proportion of students remain neutral or do not fully understand, necessitating more intensive educational.